VD_FINDINFO PC 15/12 - 14/2013 vom 17. Juli 2013 - VD Tribunal cantonal (2013)
PRESTATION COMPLÉMENTAIRE, REVENU HYPOTHÉTIQUE, AGGRAVATION DE L'ATTEINTE À LA SANTÉ | 10 LPC, 11 LPC, 2 LPC, 4 LPC, 9 LPC, 53 al. 3 LPGA, 11a OPC-AVS/AI, 14a OPC-AVS/AI